Review Of Compensation And Work Stress On Employee Performance In The Medical Records Department At Harapan Kita Heart And Blood Vessel Hospital, West Jakarta - Putra, Adittia Ammanda; Azis, Abdul (Transforma Jurnal Manajemen, 2025)
The aim of this research is to determine the effect of compensation and organizational work stress on employee performance in medical records at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta, both partially and simultaneously. The research method used is a quantitative method with a descriptive approach. The sampling technique used was saturated sampling technique, namely using a sample of 80 respondents from the entire population. The data analysis techniques used are instrument testing, classical assumption testing, linear regression analysis, coefficient of determination analysis, hypothesis testing. This is proven by the results of the compensation hypothesis test, which obtained a tcount value of 4.611 > ttable 1.990 and was strengthened by the ? value < Sig.0.05 or a significance value < 0.05 (0.000 < 0.05). Work stress obtained a tcount value of 6,152 > ttable 1.990 and strengthened by the ? value < Sig.0.05 or a significant value <0.05 (0.000 < 0.05. ) The results of research on compensation and work stress simultaneously do not have a significant effect on employee performance in medical records at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta, shown by the multiple linear regression equation Y = 9.054 + 0.314X1 + 0.476X2. This is proven by the results of simultaneous hypothesis testing obtained by the Fcount value (74.569 > Ftable 3.12) and reinforced by the significance value < 0.00 (0.000 < 0.05). The results of the coefficient of determination test for compensation and work stress variables had an influence of 65.1% on employee performance in medical records at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta. Thus H03 is accepted and H3 is rejected. This means that it is proven that there is a simultaneous insignificant influence between compensation (X1) work stress (X2) employee performance (Y)